La Mise en Oeuvre et les Mutations d’un Problème Public: les Violences Faites aux Femmes dans le Canton de Genève = Implementation and Mutations of a Public Problem : Violence Against Women in the Canton of Geneva - Roca i Escoda, Marta (Oñati Socio-Legal Series, 2015)
Violence against women (VAW) has become an issue for public action and a subject of controversy and debate in the public arena. The occurrences of VAW are - at least in part - reported by public authorities and public policies are designed to combat it, by means of prevention campaigns, setting up of shelters or counselling services. All these measures bring together a range of institutional and non-institutional actors. VAW is furthermore the focus of specific laws, but we know little about the emergence of the regulation of VAW in Switzerland. In this article, we will present preliminary results of the developpment of policies adressing domestic violence in the canton of Geneva, focusing on the political arena and analysing the definitional work done by two associations. These case studies show that the concept of gender violence has been marginalized and replaced by a new understanding of the phenomenon of gender violence, which is presented most often in a symmetrical, psychological and racialized way.